Review of Perseus Digital Library - Lang, Sarah (Enthalten in:RIDE;Köln : Institut für Dokumentologie und Editorik, [2014]-;Online-Ressource)
Abstract: Perseus Digital Library is a well-established Digital Humanities project providing a library of out-of-copyright editions of canonical world literature with a focus on the Classical languages while expanding its scope beyond its original field. Apart from being a text collection, Perseus also provides a plethora of tools for the analysis of its text material and builds upon a sound base of methodological grounding. The digital library is made up of one main collection (Greek and Roman materials) and several smaller sub-collections spanning a range of other subjects. Data acquisition is achieved semi-automatically. The contents of the library consist of out-of-print text editions, dictionaries and commentaries being enriched by the supply of digital tools for analysis. Perseus Digital Library is reviewed as a whole but a special focus of the review lies on the Greek and Roman sub-collection and sub-projects
10.18716/ride.a.8.3
Keywords: canonical text services; classics; digital library; out-of-print edition; treebank; vocabulary; word study tool